(untitled) (Agronomy Journal of Nepal, 2021)
To improve the yield of spring season maize in the inner terai of Nepal, the effect of increasing fertilizer levels for increasing planting densities on growth, yield attributes, and yield of open-pollinated maize variety were analyzed through the field experimentation in 2019. The treatments included factorial combinations of three planting densities, (a) 55556/ha, (b) 66667/ha, and (c) 83333/ha; and four fertilizers levels (research-based recommendation i.e., 120:60:40 N:P2O5:K2O kg/ha, 144:72:48 N:P2O5:K2O kg/ha, 180:90:60 N:P2O5:K2O kg/ha, and site-specific nutrient management (SSNM) based nutrient expert model recommendation i.e., 140:40:40 N:P2O5:K2O kg/ha) arranged in a split-plot design with three replications. Data on growth, yield attributes, and yield were analyzed by using R Studio. Growth was higher under the highest planting density and higher fertilizer levels applied treatments. The higher (p<0.05) heat use efficiency was recorded under the highest planting density and the higher levels of fertilizer application. The final plant population was 5.33% lower in the plant density of 55556/ha, 8.8 and 15.7% lower respectively for plant densities of 66667/ha and 83333/ha. Both the barrenness and sterility percentage were higher (p<0.05) for the highest planting densities and the lowest for the lowest plant density. Higher (p<0.05) number of kernels per cobs were recorded in the lowest plant density and the highest amount of fertilizer application. For the lowest and the highest plant densities, the leaf area index increased the grain yield whereas longer grain filling duration and less amount of barrenness and sterility increased (p<0.05) the grain yield for all plant densities. The final number of plant populations was the most important parameter to increase (p<0.05) the yield under lower plant density whereas the number of kernels per row or cob was the most important attribute to increase (p<0.05) the yield of maize under higher plant density. Due to a higher (p<0.05) number of final plant populations and comparable yield attributes, the grain yield of the highest planting density was significantly (p<0.05) higher. From the significant (p<0.05) quadratic response of plant density on the grain yield, a density of 102,950 /ha was estimated as optimum. The increased in amount of fertilizers (144:72:48 N:P2O5:K2O kg/ha, 180:90:60 N:P2O5:K2O kg/ha) gave higher grain yield. The plant densities of 66667/ha and 83333/ha were better whereas the present recommended dose of N: P2O5:K2O should be increased or need-based SSNM must be adopted to obtain the more profits from open-pollinated spring maize under the central inner Terai.